Slow expiration reduces sternocleidomastoid activity and increases transversus abdominis and internal oblique muscle activity during abdominal curl-up - Yoon, T.-L.; Kim, K.-S.; Cynn, H.-S. (Journal of Electromyography and Kinesiology, 2014)
The aim of this study was to investigate the effects of quiet inspiration versus slow expiration on sternocleidomastoid (SCM) and abdominal muscle activity during abdominal curl-up in healthy subjects. Twelve healthy subjects participated in this study. Surface electromyography (EMG) was used to collect activity of bilateral SCM, rectus abdominis (RA), external oblique (EO), and transversus abdominis/internal oblique (TrA/IO) muscles. A paired t-test was used to determine significant differences in the bilateral SCM, RF, EO, and TrA/IO muscles between abdominal curl-up with quiet inspiration and slow expiration. There were significantly lower EMG activity of both SCMs and greater EMG activity of both IOs during abdominal curl-up with slow expiration, compared with the EMG activity of both SCMs and IOs during abdominal curl-up with quiet inspiration (p < .05). The results of this study suggest that slow expiration would be recommended during abdominal curl-up for reduced SCM activation and selective activation of TrA/IO in healthy subjects compared with those in abdominal curl up with quiet inspiration.